2023
DOI: 10.1177/08862605231175515
|View full text |Cite
|
Sign up to set email alerts
|

Why Might Women Justify Dating Violence? The Role of Men’s Sexual Objectification of Their Romantic Partners Within Heterosexual Relationships

Abstract: Men’s partner-sexual objectification has been linked to increased self-objectification and diminished well-being in women. Some recent findings have also demonstrated that men’s partner-sexual objectification is related to increased violence in the relationship. However, mechanisms driving this association remain unexplored. In the present research, we collected data on women and men involved in heterosexual romantic relationships and investigated the associations between men’s partner-sexual objectification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Rudman and Mescher (2012) demonstrated that men who implicitly dehumanize women (as animals and objects) are also likely to rape and sexually harass them. Additionally, several studies (Bevens & Loughnan, 2019; Morera et al, 2022; Pecini et al, 2023) confirmed that dehumanization is associated with abuse in romantic relationships, greater dating violence, and more sexual aggression towards women.…”
Section: Biologization and Indirect Aggressionmentioning
confidence: 97%
“…Rudman and Mescher (2012) demonstrated that men who implicitly dehumanize women (as animals and objects) are also likely to rape and sexually harass them. Additionally, several studies (Bevens & Loughnan, 2019; Morera et al, 2022; Pecini et al, 2023) confirmed that dehumanization is associated with abuse in romantic relationships, greater dating violence, and more sexual aggression towards women.…”
Section: Biologization and Indirect Aggressionmentioning
confidence: 97%